Case Report: Compromised Airway Following Anesthesia and Its Correlation With the Use of ACE Inhibitors—An Unexpected Clinical Event and Review of Literature - Mohanty, Sanjeev; Bangaari, Ashish; Gnanasekaran, Kumaran (Frontiers in Surgery, 2021)
A known risk for patients taking angiotensin converting enzyme-inhibitors (ACE-I) is angioedema caused by bradykinin, that can involve the face, lips, tongue and upper airway. Since the clinical presentation is variable and unpredictable, with no possibilities to prevent and predict its development, the diagnosis can be delayed potentially translating into increased patient suffering and risk of suffocation. The clinical uncertainty and the rapidity of airway compromise raised an alarm and thus being reported to raise the awareness of health care professionals sharing the common unified airway and propose preventive attitudes for discussion that could improve the perioperative safety of patients